Dynamic mobile agent migration in Wireless Sensor Networks. (7th December 2006) - Xu, Yingyue; Qi, Hairong
Computing paradigm plays an important and fundamental role in collaborative processing in Wireless Sensor Networks (WSN). The client/server based paradigm and the mobile agent based paradigm are two popular computing models used to facilitate collaboration among sensor nodes. We study the key problem of determining mobile agent itinerary for collaborative processing and models the Dynamic Mobile Agent Planning (DMAP) problem. We then present two itinerary planning algorithms with the goal of maximising the information extracted while keeping resource usage to a minimum. The ISMAP determines the itinerary before dispatching the mobile agent while the IDMAP algorithm selects the route on the fly. We design three metrics (energy consumption, network lifetime, and the number of hops) and use simulation tools to quantitatively measure the performance of different itinerary planning algorithms. Simulation results show considerable improvement over the ISMAP using the IDMAP itinerary algorithm.